2017
DOI: 10.1016/j.ijsu.2017.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Intra-capsular total thyroid enucleation versus total thyroidectomy in treatment of benign multinodular goiter. A prospective randomized controlled clinical trial

Abstract: Intracapsular Total thyroid enucleation technique is safe with the least serious complications, especially RLN injury and hypoparathyroidism, with no recurrence, but this technique still not radical so couldn't be used in suspicious cases for malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, the possibility of recurrence and the need for a completion thyroidectomy if the final histology is cancer, are important considerations. For these reasons, the 2016 guidelines and meta-analysis recommended total thyroidectomy for both toxic and non-toxic benign multinodular goiter [58,59]. Total thyroidectomy can now be performed as safely as lobectomy and subtotal thyroidectomy are performed, because of improved surgical techniques and experience [50,60].…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibility of recurrence and the need for a completion thyroidectomy if the final histology is cancer, are important considerations. For these reasons, the 2016 guidelines and meta-analysis recommended total thyroidectomy for both toxic and non-toxic benign multinodular goiter [58,59]. Total thyroidectomy can now be performed as safely as lobectomy and subtotal thyroidectomy are performed, because of improved surgical techniques and experience [50,60].…”
Section: Discussionmentioning
confidence: 99%
“…Sewefy et al made study on 224 patients 112 patients underwent intracapsular total thyroidectomy and 112 patients underwent extracapsular total thyroidectomy and found that by intracapsular method the complication of recurrent laryngeal nerve injury was 0% compared to 0.9% in extracapsular method and permanent hypocalcaemia was 0% in intracapsular method compared to 0.9% in extracapsular method. 11 Meer et al made retrospective study on patients on tertiary care center and complications was counted from this technique and found that 0% cases complicated from permanent recurrent laryngeal nerve damage and temporary neuropraxia was around 0.5% and The incidence of temporary and permanent hypocalcaemia was found to be around 0.7% and 0.2% respectively. 12 Dong y et al made retrospective study on 44 patients underwent thyroid capsular dissection and the result was 1 patient suffered from postoperative hoarseness of voice.…”
Section: Discussionmentioning
confidence: 99%
“…14 All of these studies suggest that the new technique is easy to learn and do by junior surgeons which make it perfect choice in secondary health centres like central hospital in which study was made because the previous studies was done only in highly specialized centres like universities hospitals or endocrine surgery centres only. 11 In the new technique time in searching for recurrent laryngeal is saved as in intracapsular dissection no time spent in searching for recurrent laryngeal nerve or parathyroid glands. 14…”
Section: Discussionmentioning
confidence: 99%
“…None of the studies got the highest stars i.e., 9 and all observational studies remained between five and three stars. One randomized control trial by Sewefy et al 21 was analyzed by the Cochrane Risk of Bias tool for randomized studies 25 and had a high risk of bias as the blinding of participants and personnel was not specified (performance bias).…”
Section: Methodsmentioning
confidence: 99%